Novel large deployable antenna backing structure concepts for foldable reflectors - Fraux, V; Lawton, M; Reveles, JR; You, Z (Springer Verlag, 2013)

(untitled)
This paper describes a number of large deployable antenna (LDA) reflector structure concepts developed at EnerSys-ABSL. Furthermore, EnerSys-ABSL has confirmed the desire to build a breadboard demonstrator of a backing deployable structure for a foldable reflector in the diameter range of 4–9 m. As part of this project EnerSys-ABSL has explored five novel deployable structure concepts. This paper presents the top level definition of these concepts together with the requirements considered in the design and selection of the preferred candidate. These new concepts are described and then compared through a trade-off analysis to identify the most suitable concept that EnerSys-ABSL would like to consider for the breadboard demonstrator. Finally, the kinematics of the chosen concept is described in more detail and future steps in the development process are highlighted.